SGLT2 Inhibitors and how they work beyond the glucosuric effect. State of the art (2024)
Type 2 diabetes mellitus (T2DM) is associated with a heightened risk of cardiovascular and renal complications. While glycemic control remains essential, newer therapeutic options, such as SGLT2 inhibitors, offer additional benefits beyond glucose reduction. This review delves into the mechanisms underlying the cardio-renal protective effects of SGLT2 inhibitors. By inducing relative hypoglycemia, these agents promote ketogenesis, optimize myocardial energy metabolism, and reduce lipotoxicity. Additionally, SGLT2 inhibitors exert renoprotective actions by enhancing renal perfusion, attenuating inflammation, and improving iron metabolism. These pleiotropic effects, including modulation of blood pressure, reduction of uric acid, and improved endothelial function, collectively contribute to the cardiovascular and renal benefits observed with SGLT2 inhibitor therapy. This review will provide clinicians with essential knowledge, understanding, and a clear recollection of this pharmacological group’s mechanism of action.